The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0272684x20972642
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Media Literacy: Is There Any Relation?

Abstract: Background The health information is an important factor for improving people's health behaviors. On the other hand, media literacy plays an important role in the search and selection of valid information and resources about health. Therefore, the present study aimed to investigate the correlation between health literacy and media literacy. Method This study was a cross-sectional study. Random cluster sampling was used to select 700 citizens in Kerman, Iran. Health literacy for Iranian adults’ questionnaire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In line with the aforementioned findings, Namazi (9) showed that the majority of students mentioned the Internet as their main source of health information. Parandeh Afshar et al (53) and Mahmoudi and Taheri (54) also reported their participants mostly received health information via the Internet.…”
Section: Discussionmentioning
confidence: 98%
“…In line with the aforementioned findings, Namazi (9) showed that the majority of students mentioned the Internet as their main source of health information. Parandeh Afshar et al (53) and Mahmoudi and Taheri (54) also reported their participants mostly received health information via the Internet.…”
Section: Discussionmentioning
confidence: 98%
“…The information source indicator was mainly used to reflect the ubiquitous role of the Internet in ensuring that people can conveniently access knowledge and consultations about their health. This access to information ultimately serves to improve daily living habits and detect changes in individuals’ health status as early as possible [ 29 ]. Finally, as for the dependent variable, we simplified some of the measurement options for some of the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Mass media contains information that offers health guidance, as well as implicit and explicit relevant content from commercial entities or health systems that can be either health-promoting or healthcompromising [31]. Therefore, researchers have proposed the concept of media health literacy, and noted that it is an important determinant of health literacy [31][32][33][34]. A lack of originality and excessive advertisements or entertainment factors used to be serious limitations of China's healthcare television programs, which affected the authenticity of health knowledge and reduced public reliability.…”
Section: Information Channels and Health Literacymentioning
confidence: 99%